CRITICAL THINKING SKILL: KONSEP DAN INIDIKATOR PENILAIAN - Ratna Hidayah; Moh. Salimi; Tri Saptuti Susiani (Universitas Sarjanawiyata Tamansiswa, 2017)
The world development of the 21st century is marked by the progress and the demands of technologies, which may lead to regression. Life in the 21st century demands a person to master a range of skills. One of the important skills in the 21st century is critical thinking skill. This study focuses on the definition, importance, challenges in developing indicators and assessment of critical thinking skills. Critical thinking skill is the ability to think logically, reflectively, productively and systematically appeared in making consideration and making the best decision. Critical thinking skills are beneficial in improving the analysis skill, creativity, ability to make use of ideas or information, and looking for information skill as well as self-reflection. Learning can do the development of learners’ critical thinking skills. An important indicator in the critical thinking skills is interpreting which about an ability dealing with studying or analyzing, identifying the relevant or irrelevant sources, identifying and evaluating the assumptions, implementing various strategies to make the appropriate decisions, summarizing and regulating themselves.